2012
DOI: 10.1371/journal.pone.0036661
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Larvae Exhibit Rheotaxis and Can Escape a Continuous Suction Source Using Their Lateral Line

Abstract: Zebrafish larvae show a robust behavior called rheotaxis, whereby they use their lateral line system to orient upstream in the presence of a steady current. At 5 days post fertilization, rheotactic larvae can detect and initiate a swimming burst away from a continuous point-source of suction. Burst distance and velocity increase when fish initiate bursts closer to the suction source where flow velocity is higher. We suggest that either the magnitude of the burst reflects the initial flow stimulus, or fish may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 21 publications
6
81
0
Order By: Relevance
“…The authors confirmed that, consistent with previous studies [4][5][6] , the zebrafish could position themselves in the tube away from the walls and orient their bodies to swim against the direction of water flow (Fig. 1).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The authors confirmed that, consistent with previous studies [4][5][6] , the zebrafish could position themselves in the tube away from the walls and orient their bodies to swim against the direction of water flow (Fig. 1).…”
supporting
confidence: 90%
“…However, real aquatic environments present other challenges, such as 3D flow that cannot be navigated solely with turns in a hori zontal plane. In addition, the Kelvin-Stokes theorem that underlies the proposed navigation strategy can fail if there are local sources or sinks of water in the vicinity, such as the suction flow that some predators use to ingest prey 4 . Paradoxically, the proposed mechanism for rheotaxis could also lead fish towards regions of flow that, although they exhibit small flow gradients, could simultaneously have large, uniform flow speeds that overpower the fish's ability to escape such strong currents.…”
Section: News and Viewsmentioning
confidence: 99%
“…Even at low light levels and overcritical currents, they may respond to hydraulic gradients and drift under certain conditions (Kaminskas 2011;Schludermann et al 2012). Experiments on zebrafish larvae (Danio rerio, Cyprinidae), for instance, showed that rheoreaction is mediated by neuromasts of the lateral line, which enables young fish to sense water flows and orient in currents at night (Olszewski et al 2012;Stewart et al 2013).…”
Section: Active Driftmentioning
confidence: 99%
“…The neuromasts of larval zebrafish are readily quantifiable; however, the lateral line of the adult zebrafish has a much greater number of neuromasts per stitch making quantitative analyses more difficult 6,17,19,20 . As seen in Figure 1A, the head has a significantly higher number of neuromasts compared to either the mid-section or tail; with the tail region having the least number of neuromasts as shown in Figure 1D.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The lateral line (LL) system is a mechanosensory organ found in both fish and amphibians that is responsible for hearing, balance, rheotaxis and mediating behaviors such as schooling and predator avoidance [1][2][3][4][5] . It is composed of clusters of hair cells surrounded by supporting cells, both of which are positioned in structures called neuromasts 6 .…”
Section: Introductionmentioning
confidence: 99%